Programming the finite element method - Smith, I. M. (Ian Moffat), 1940-; Griffiths, D. V.; Margetts, Lee (Chichester, West Sussex, UK : Wiley, 2014)
"Provides an updated version of Fortran 2003 (all the Fortran programs and subroutines are listed in full in the text but will also be made available online)"--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Finite element method -- Data processing; Engineering -- Data processing; FORTRAN 2003 (Computer program language); TECHNOLOGY & ENGINEERING / Drafting & Mechanical Drawing; Engineering -- Data processing; Finite element method -- Data processing; FORTRAN 2003 (Computer program language); Electronic books; Electronic books